THE APPLICATION OF LITERATURE TO TRAIN THE STUDENTS’ CRITICAL REASONING IN SDS JAI NALANDA, JAMBI CITY - Tri Yudha Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2022)
This study aims to describe the application of literacy in training students in class II SDS Jai Nalanda Jambi City. This research is a qualitative research and with descriptive analysis. The informants in this study were class II teachers. The results showed that several stages carried out by class II teachers at SDS Jai Nalanda Jambi City consisted of three stages, namely 1) Mini Lesson Stage which included apperception and strategy demonstrations, 2) Conferring Stage was the application of strategies and discussions in pairs/groups and questions. lighter 3) Sharing stage, namely the stage where students make presentations on the results that have been obtained and provide responses to one another. In training students to think critically, the teacher uses books as the main source in learning with critical questions.